2023
DOI: 10.1128/spectrum.02363-22
|View full text |Cite
|
Sign up to set email alerts
|

White Spot Syndrome Virus (WSSV) Inhibits Hippo Signaling and Activates Yki To Promote Its Infection in Penaeus vannamei

Abstract: White spot syndrome virus (WSSV) is one of the most harmful viral pathogens to shrimp. The pathological mechanism of WSSV infection remains unclear to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…The Hippo signalling pathway is important for a variety of biological processes and is extensively involved in mammalian immunity, but little is known about its role in infectious diseases in invertebrates (Fu et al, 2022). A recent study showed that WSSV can inhibit Hippo signalling and activates Yki to promote its infection in L. vannamei (Yang et al, 2022). In the present study, the Hippo signalling pathway was strongly activated at 24 hpi.…”
Section: Discussionmentioning
confidence: 99%
“…The Hippo signalling pathway is important for a variety of biological processes and is extensively involved in mammalian immunity, but little is known about its role in infectious diseases in invertebrates (Fu et al, 2022). A recent study showed that WSSV can inhibit Hippo signalling and activates Yki to promote its infection in L. vannamei (Yang et al, 2022). In the present study, the Hippo signalling pathway was strongly activated at 24 hpi.…”
Section: Discussionmentioning
confidence: 99%